Fructose promotes pyoluteorin biosynthesis via the CbrAB-CrcZ-Hfq/Crc pathway in the biocontrol strain Pseudomonas PA1201 - Ying Cui; Kai Song; Zi‐Jing Jin; Learn−Han Lee; Chitti Thawai; Ya‐Wen He (Synthetic and Systems Biotechnology, 2023)
induction. Mechanistically, fructose-mediated Plt synthesis involved carbon catabolism repression. The two-component system CbrA/CbrB and small RNA catabolite repression control Z (crcZ) were essential for fructose-induced Plt synthesis. The small RNA binding protein Hfq and Crc negatively regulated fructose-induced Plt. Taken together, this study provides a new model of fructose-dependent Plt production in PA1201 that can help improve Plt yield by biosynthetic approaches.
Keywords: Microbial Community Ecology and Physiology; Genomics and Phylogenetic Studies; Microbial Fuel Cells and Bioremediation